Plyometric training: A Systematic review on volume and intensity in high-level volleyball - Nelson Kautzner Marques Junior; Illoleicys Rodriguez Pinillo (spdfharmony.com, 2025)
Background: Plyometric training was originally practiced in European athletics from 1919 to 1930. Plyometric training involves the athlete practicing several jumps. In 1964, plyometric training began to be practiced in other sports. In 1976 and 1977, plyometrics was used during the Italian championship. Aims: This systematic review was to determine the volume and intensity of the plyometric training for high-level volleyball. Methods: This study followed the PRISMA methodology. The articles were selected from January to July 2024, totaling 24 articles to ensure research quality. The printed articles and books were e-mailed to the author by his Italian colleague G. B. After collecting the scientific books and articles, the author wrote the results. Result: The systematic review identified an optimal training frequency of 2 to 3 weeks for male and female athletes. The recommended plyometric training for males consisted of 2–8 sets of 4–20 jumps, with rest intervals ranging from 15 seconds to 5 minutes and jump heights between 20–110 cm. For females, the suggested regimen included 2–7 sets of 5–15 jumps, with similar rest intervals and jump heights between 20–80 cm. In addition to plyometric training, both groups were advised to engage in bodybuilding exercises focused on developing maximum and explosive strength. The article also provided detailed recommendations on exercise types (e.g., horizontal jumps, tuck jumps, drop jumps, hurdle jumps) and appropriate training volume and intensity for plyometric workouts. Conclusion: Plyometric training is a very important strength training for the volleyball player because it improves several motor capacities.